Laparoscopic Diagnosis and Laparoscopic Hyperthermic Intraoperative Intraperitoneal Chemotherapy for Pseudomyxoma Peritonei Detected by CT Examination - Masamitsu Hirano; Yutaka Yonemura; Emel Canbay; Masumi Ichinose; Tuyoshi Togawa; Takayuki Matsuda; Nobuyuki Takao; Akiyoshi Mizumoto (Gastroenterology Research and Practice)
Background. Patients with early stage of pseudomyxoma peritonei (PMP) are sometimes difficult to diagnose the primary sites and intraperitoneal spread of tumor and to perform a cytological study. Methods. Patients without a definitive diagnosis and with unknown extent of peritoneal spread of tumor underwent laparoscopy. Hyperthermic intraoperative intraperitoneal chemotherapy (HIPEC) was administered as part of the same intervention. The results of treatment were evaluated at the time of second-look laparotomy (SLL) as a subsequent intervention. Results. Eleven patients were managed by diagnostic laparoscopy followed by laparoscopic HIPEC (LHIPEC). The operation time of laparoscopic examination and LHIPEC was 177 ± 26 min (range 124–261 min). No intraoperative complication was experienced. The peritoneal carcinomatosis index (PCI) score by laparoscopic observation was 16.5 ± 6.4 (range 0–30). One patient with localized pseudomyxoma peritonei (PMP) mucocele did not received LHIPEC; the other 10 patients with peritoneal metastases (PM) were treated with LHIPEC. After LHIPEC, ascites disappeared in 2 cases and decreased in the amount in the other 8 cases. Nine patients underwent SLL and cytoreductive surgery (CRS) combined with HIPEC. The duration between LHIPEC and SLL ranged from 40 to 207 days (97 ± 40 days). The PCI at the SLL ranged from 4 to 27 (12.9 ± 7.1). The PCI at the time of SLL decreased as compared to PCI at the time of diagnostic laparotomy in 7 of 9 patients. Median follow-up period is 22 months (range 7–35). All 11 patients are alive. Conclusion. The early results suggest that laparoscopic diagnosis combined with LHIPEC is useful to determine the surgical treatment plan and reduce the tumor burden before definitive CRS at SLL.